Diagnóstico do usuário no aprimoramento dos serviços de tecnologia da informação: um projeto de intervenção para o Ministério Público do Estado do Rio Grande do Norte - Monteiro, Edilson Brito (2014)
The information tecnology (IT) has, over the years, gaining prominence as a strategic element and competitive edge in organizations, public or private. In the judiciary, with the implementation of actions related to Judiciário Eletrônico, information technology (IT), definitely earns its status as a strategic element and significantly raises the level of dependence of the organs of their services and products. Increasingly, the quality of services provided by IT has direct impact on the quality of services provided by the agency as a whole. The Ministério Público do Estado do Rio Grande do Norte (MPRN) deployments shares of Electronic Government, along with an administrative reform, beyond these issues raised, caused a large increase in institutional demand for products and services provided by the Diretoria de Tecnologia da Informação (DTI), a sector responsible for the provision of IT services. Taking as starting point strategic goal set by MPRN to reach a 85% level of user satisfaction in four years, we seek to propose a method that assists in meeting the goal, respecting the capacity constraints of the IT sector. To achieve the proposed objective, we conducted a work in two distinct and complementary stages. In the first step we conducted a case study in MPRN, in which, through an internal and external diagnosis of DTI, accomplished by an action of internal consulting and one research of the user satisfaction, we seek to identify opportunities of change seeking to raise the quality perceived of the services provided by the DTI , from the viewpoint of their customers. The situational report, drawn from the data collected, fostered changes in DTI, which were then evaluated with the managers. In the second stage, with the results obtained in the initial process, empirical observation, evaluation of side projects of quality improvement in the sector, and validation with the managers, of the initial model, we developed an improved process, gazing beyond the identification of gaps in service a strategy for the selection of best management practices and deployment of these, in a incremental and adaptive way, allowing the application of the process in organs with little staff allocated to the provision of information technology services